Nanoengineered polymeric capsules as elements of unconventional computing systems. Issue 1 (19th November 2014) - Erokhina, Svetlana; Pastorino, Laura
Abstract Nanoengineered polymeric capsules are smart objects with a shell of 4‐20 nm thick and a core volume, that can be filled with the different substances. The capsules can be delivered to a desirable place and the encapsulated material release can be triggered by the variation of the environmental medium parameters or by the external action. In this paper, we present important steps of the capsule preparation and discuss how they can be used in the field of chemical and bio‐chemical unconventional computer systems. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)